Efficacy of Andrographis paniculata leaf extract as a green corrosion inhibitor for mild steel in concentrated sulfuric acid: Experimental and computational insights - Femiana Gapsari; Putu H. Setyarini; Khairul Anam; Saprizal Hadisaputra; Syarif Hidayatullah; Purnami; Abdul Mudjib Sulaiman; Chin Wei Lai (Results in Surfaces and Interfaces)
The rising demand for eco-friendly corrosion inhibitors has intensified efforts to find sustainable alternatives to hazardous chemical inhibitors widely used in industry. Mild steel, although commonly utilized in acidic environments, is prone to significant corrosion, necessitating effective solutions to prevent structural degradation. This study investigates the potential of Andrographis paniculata leaf extract (APLE) as a sustainable, green corrosion inhibitor for mild steel in concentrated sulfuric acid, a condition representative of harsh industrial environments. Using electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization (PDP) methods, APLE demonstrated a high inhibition efficiency of 95.14% at a concentration of 4000 ppm, effectively reducing both anodic and cathodic corrosion reactions. Scanning electron microscopy (SEM) revealed a protective layer formation on the steel surface, significantly reducing corrosion. The adsorption of APLE followed the Langmuir isotherm, indicating monolayer coverage, while quantum chemical calculations validated APLE's electron-donating capability, enhancing surface stability through physisorption. These findings underscore APLE as a viable, eco-friendly alternative to conventional inhibitors, offering promising applications in various acidic environments.